2021
DOI: 10.1182/bloodadvances.2021005139
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cryopreservation and transit times of allogeneic grafts on hematopoietic and immune reconstitution

Abstract: We sought to evaluate the impact of cryopreservation of unrelated donor peripheral blood stem cell (PBSC) grafts on engraftment, chimerism, and immune reconstitution in the context of the Covid-19 pandemic. We reviewed stem cell product characteristics and clinical outcomes in 101 patients receiving cryopreserved PBSCs from unrelated donors (URD) between January 1, 2019, and December 31, 2020, compared with 203 patients receiving fresh URD PBSCs. We observed no differences in 6-month overall survival, progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 26 publications
1
27
0
4
Order By: Relevance
“…Logistic challenges were one of the drivers in the consideration to cryopreserve donations, due to the uncertain timings of deliveries dependent on airplanes and trains subject to delays or cancellations. Reassuringly, we did not see significant differences in the average times from collection to delivery, although others have reported increased times for international transfers 12 . There was not an evident shift to local collections over the relatively brief window of the survey period, and the WMDA report for 2020 noted only a small decrease in the proportion of donations not crossing national borders 20 .…”
Section: Discussionmentioning
confidence: 45%
“…Logistic challenges were one of the drivers in the consideration to cryopreserve donations, due to the uncertain timings of deliveries dependent on airplanes and trains subject to delays or cancellations. Reassuringly, we did not see significant differences in the average times from collection to delivery, although others have reported increased times for international transfers 12 . There was not an evident shift to local collections over the relatively brief window of the survey period, and the WMDA report for 2020 noted only a small decrease in the proportion of donations not crossing national borders 20 .…”
Section: Discussionmentioning
confidence: 45%
“…Recent papers have emphasized the importance of transit time. In a recent study at Dana Farber Cancer Institute, researchers looked at outcomes of 101 recipients who received cryopreserved grafts and found that grafts >48 h old at the time of cryopreservation or infusion significantly increased risk of graft failure (hazard ratio = 4.57; 95% confidence interval, 1.71–12.3; p = .0025) ( 8 ). However, the travel restrictions may occasionally result in products delivery exceeding the 72-h limit.…”
Section: Discussionmentioning
confidence: 99%
“…Although HSPC grafts can be used fresh, modern routines often rely on cryobanking of BM, CB and PB grafts [ 50 54 ]. Particularly, CB and PB grafts are often stored cryobanked until clinical use [ 51 , 55 57 ]. Experience during the COVID-19 pandemic suggests that even in the well-established HSCT setting, cryopreservation and increased transit times can detrimentally affect immune reconstitution [ 57 , 58 ].…”
Section: Hematopoietic Stem and Progenitor Cells (Hspcs)mentioning
confidence: 99%